The Mind development - Hutton, Richard; Jackson, Eisa. (New York WNET, 1988)
Tracing specific brain cells, it follows the human brains development from a single cell to a six-year-old brain. Computer graphics, time-lapse micro-photography and in utero footage give you detailed images of the development of the human fetus. Experiments reveal that a fetus actively prepares from survival before birth.
VHS
Keywords: Brain; Brain -- Localization of functions; Psychology